1978
DOI: 10.1159/000112578
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro </i>Formation of Piperidine, Cadaverine and Pipecolic Acid in Chick and Mouse Brain during Development

Abstract: We have demonstrated for the first time in vitro formation of cadaverine and pipecolid acid from L-lysine in (a) chick embryos and chick embryo heads at 3–7 days of incubation (d.i.) and 5–7 d.i., respectively; (b) brain of chick embryos from 11 d.i. to 30 days after hatching (d.a.h.) for cadaverine and from 20 d.i. to 30 d.a.h. for pipecolic acid; (c) mouse brain from 2 days after birth up to 3 months after birth; and (d) mouse embryos at days 17–20 of gestation for cadaverine and at days 13 and 17 of gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 14 publications
0
16
1
Order By: Relevance
“…Pipecolic acid is a major intermediate of Lys metabolism in the mammalian (Schmidt-Glenewinkel et al 1977;Giacobini et al 1980) and chick brain (Nomura et al 1978). The detected metabolites were divided into three groups by comparing levels in the Lys150% and Lys100% groups: up-regulated (> 1.2-fold of Lys100%), downregulated (< 0.8-fold) and no change (0.8-1.2).…”
Section: Discussionmentioning
confidence: 99%
“…Pipecolic acid is a major intermediate of Lys metabolism in the mammalian (Schmidt-Glenewinkel et al 1977;Giacobini et al 1980) and chick brain (Nomura et al 1978). The detected metabolites were divided into three groups by comparing levels in the Lys150% and Lys100% groups: up-regulated (> 1.2-fold of Lys100%), downregulated (< 0.8-fold) and no change (0.8-1.2).…”
Section: Discussionmentioning
confidence: 99%
“…This spike in l -pipecolate levels almost exactly mirrors the change in NADPH-dependent T 3 -binding protein concentrations noted at birth. Synthesis of l -pipecolate from l -lysine has been shown to be accelerated in the perinatal period in chick and mouse brain homogenates and this may also correlate with the observed changes in l -pipecolate levels (Nomura et al 1978). It is interesting to note that by day 10 in rats, brain l -pipecolate is markedly decreased from its maximum just after birth (Nishio and Segawa 1983; Kim and Giacobini 1985).…”
Section: μ-Crystallin: the First P2c Reductase Identified In Mammaliamentioning
confidence: 99%
“…Lpipecolic acid (L-PA) is a major metabolic DL-tryptophan attenuates stress in chicks 27 intermediate of L-lysine in the mammalian (Schmidt-Glenewinkel et al, 1977;Giacobini et aZ. , 1980) and chicken brain (Nomura et al, 1978). Takagi et al (2001) reported that the i.c.v.…”
Section: Resultsmentioning
confidence: 99%